Mobile Commerce and Mobile Payment: A Study on Islamic Perspective (IIUC Studies, 2012)
Electronic commerce, very important part of Information and Communication Technologies (ICT), is one of the most common business terms in use in 21st century. Developed countries are more popular because of their rapid growth of ICT, e-commerce and online transaction. But in developing or under develop countries the scenario is different. Technical laggings, dearth of infrastructure, infeasibility of the existing frameworks and people apathy are the main reasons behind this. There are several alternative ways of e-commerce and online transaction. Mobile payment, a way of online transaction, may be beneficial way of payment for developing countries because of its mobile network infrastructure. In this paper, a model of electronic payment system for M-Commerce has been proposed and analyzed the security for the system. This proposal may be suitable for developing countries where mobile phones are available but other e-payment tools like debit and credit cards are not much available. It also identifies what Islam has to say about our current use of M-Commerce and the way Islam can offer guidance for its use in the future. The paper also touches on the conditions and criteria that must be met in order to make an M-Commerce transaction acceptable under Islamic perspective. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12257 IIUC Studies Vol.7 2011: 37-48